2017
DOI: 10.1093/brain/awx326
|View full text |Cite
|
Sign up to set email alerts
|

A novel human pain insensitivity disorder caused by a point mutation in ZFHX2

Abstract: Studies of monogenic heritable pain disorders provide valuable insights into human pain mechanisms. Habib et al. show that a point mutation in the gene ZFHX2 causes an autosomal dominant form of pain insensitivity. Modulating ZFHX2 and/or downstream genes may present a new strategy for the treatment of chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 49 publications
(59 reference statements)
0
28
0
1
Order By: Relevance
“…In the regions under putative selection we looked for genes that could be related to adaption of Russian sheep breeds to local environments ( Table 2). We noticed that five breeds: Karachaev, Krasnoyarsk, Lezgin, Salsk, and Altai Mountain had a common signature of selection reported by the DCMS method near the ZFHX2 (zinc finger homeobox 2), a gene which was shown to be responsible for an inability to feel pain in humans (including low and high temperatures) [26]. The same authors report that ZFHX2 knock-out mice had significantly higher acute thermal pain thresholds [26].…”
Section: Candidate Genes For Adaptation Of the Russian Sheep Breeds Tmentioning
confidence: 96%
“…In the regions under putative selection we looked for genes that could be related to adaption of Russian sheep breeds to local environments ( Table 2). We noticed that five breeds: Karachaev, Krasnoyarsk, Lezgin, Salsk, and Altai Mountain had a common signature of selection reported by the DCMS method near the ZFHX2 (zinc finger homeobox 2), a gene which was shown to be responsible for an inability to feel pain in humans (including low and high temperatures) [26]. The same authors report that ZFHX2 knock-out mice had significantly higher acute thermal pain thresholds [26].…”
Section: Candidate Genes For Adaptation Of the Russian Sheep Breeds Tmentioning
confidence: 96%
“…Interestingly, a recent study found a pain insensitivity disorder caused by a mutation in ZFHX2 (Habib et al 2017), which carries an AHMC, and three HHMCs are observed in NPAP1, which might be associated with the Prader-Willi syndrome, involving behavioral problems and a high pain threshold (Buiting et al 2007). Such changes may point to differences in levels of resilience to pain between Neanderthals and modern humans.…”
Section: Life History and Other Phenotypic Traitsmentioning
confidence: 99%
“…This congenital hypoalgesia is a rare inherited disorder. A human pain insensitivity disorder is caused by a point mutation in ZFHX2 gene (Habib et al, 2018). There is no peripheral neuropathy in the family.…”
Section: Zfhx2 Genementioning
confidence: 99%